EMPIRICAL ASSESSMENT OF THE IMPACT OF INFORMATION TECHNOLOGY SYSTEM ON BANKING IN GHANA - Liu, Ruiwen; Duduchogeb, Thomas Thompson; Duduchogea, Solomon (IJRDO - Journal of Business Management, 2017)
We explores the impact of the introduction of Information Technology and Information Systems (IT/IS) into the African banking sector and the Ghanaian High Street Banking in particular and how these technological advancements have gone a long way in changing the face of the banking industry in Africa. The study indicates that Ghana inherited its administrative structure from the Europeans who at a point in time ruled the country. The research concluded that the introduction of IT/IS technology has been generally accepted by the customers. Though Electronic funds transfer has been around for a number of years, only 4.9% of the clients are of the view that it has not caught up with customers due to the fact that it is generally not real time transaction as it needs to be reloaded any time the customer’s account is used up. Among all the electronic banking systems in place, the ATM seems to be the most popular system of delivery with the banking industry with telephone banking catching up gradually as a result of the increasing use of mobile phones and fixed phone lines. Internet Banking is not very popular channel due to the low internet connectivity in the country.